Advances in Development of Radiometal Labeled Amino Acid-Based Compounds for Cancer Imaging and Diagnostics - Mária Bodnár Mikulová; Peter Mikuš (MDPI AG, 2021)
Radiolabeled biomolecules targeted at tumor-specific enzymes, receptors, and transporters in cancer cells represent an intensively investigated and promising class of molecular tools for the cancer diagnosis and therapy. High specificity of such biomolecules is a prerequisite for the treatment with a lower burden to normal cells and for the effective and targeted imaging and diagnosis. Undoubtedly, early detection is a key factor in efficient dealing with many severe tumor types. This review provides an overview and critical evaluation of novel approaches in the designing of target-specific probes labeled with metal radionuclides for the diagnosis of most common death-causing cancers, published mainly within the last three years. Advances are discussed such traditional peptide radiolabeling approaches, and click and nanoparticle chemistry. The progress of radiolabeled peptide based ligands as potential radiopharmaceuticals is illustrated via novel structure and application studies, showing how the molecular modifications reflect their binding selectivity to significant onco-receptors, toxicity, and, by that, practical utilization. The most impressive outputs in categories of newly developed structures, as well as imaging and diagnosis approaches, and the most intensively studied oncological diseases in this context, are emphasized in order to show future perspectives of radiometal labeled amino acid-based compounds in nuclear medicine.